Storage duration and temperature affect pathogen load, heavy metals, and nutrient levels in faecal derived fertiliser - Nartey, Eric Gbenatey; Sakrabani, R.; Tyrrel, S.; Cofie, Olufunke O. (Informa UK Limited, 2024)
There are debates regarding the safety of faecal derived fertiliser (FDF) due to notions that harmful substances may persist at undetectable levels. A major concern is the recolonisation of indigenous pathogens and nutrient changes while undergoing storage. Abiotic factors such as duration and temperature on indigenous pathogen re-growth and nutrient during FDF storage have received little research attention. In this study, we assess the effect of varying storage temperature conditions and duration on indigenous E. coli re-growth and NPK changes of different FDF (enriched co-compost, NECo and co-compost, Co) during storage. A 2 × 3 × 6 factorial design was used with factors: fertiliser, temperature, and duration. The factorial had 36 experimental conditions in a completely randomised design with three replications. FDF samples were collected monthly for 6 months and analysed for pH, EC, organic carbon, N, NH4-N, NO3-N, P, K, E. coli, and total coliform. Findings show storage temperature and duration did not affect indigenous E. coli re-growth and total N in stored NECo and Co. However, NH4-N concentrations of NECo decreased between 27% and 55% with increasing duration of storage at lower temperatures (5°C and 25°C). The significance of this study for the FDF industry is that it is safe after storage and longer storage do not necessarily influence nutrient losses in stored FDF. Future studies are recommended to investigate the effect of moisture on stored FDF.